Upaya Meningkatkan Keaktifan Belajar Peserta Didik Pada Pembelajaran Fisika Melalui Model Pembelajaran Berbasis Masalah - Irmawati, Irmawati; Suarti, Suarti; Nurlina, Nurlina (UIN Alauddin Makassar, 2021)
This research conducted action research (classroom action research) in addition, to solve the problem of active physics learning in class.The research subjects used were students of class X electricity at SMK Negeri 6 Takalar even semester of the 2015/2016, totaling 22 students. This research was conducted in two cycles and at the end of each cycle a reflection was made of the actions given.Data collection techniques in this study used observation sheets, daily journals and questionnaires for student responses.The results showed that the implementation of learning using problem-based learning models in physics subjects could increase the learning activeness of students, such as 1) students pay attention to the explanations of teachers and other students in cycle I by 65.53% to 82.57% in cycle II, 2) students who are active in discussion activities during the learning process from cycle I are 65.52%. to 77.64% in cycle II, 3) students dare to ask questions from 45.83% to 66.29% in cycle II, 4) Dare to ask questions in cycle I amounted to 46.97% to 68.18% per cycle II, 5) Students are able to solve problems in cycle I from 58.71% to 74.24% in cycle II.